Production of seedlings under saline stress in different environments and substrates - de Oliveira Santos, Samuel; Gomes de Sousa, Geocleber; Matos da Cruz Filho, Elizeu; Barroso da Silva Junior, Francisco; Ferreira Goes, Geovana; Castelo Sousa, Henderson; Ribeiro Gomes, Krishna; Nascimento Leite, Kelly (Comunicata Scientiae, 2023)
The interaction between agricultural environment and alternative substrates can attenuate salt stress in zucchini seedlings. Based on that, the objective of this work was to evaluate the production of zucchini seedlings irrigated with saline water and cultivated in different types of environments and substrates. The experimental design was completely randomized, using a split-split plots scheme, with the plot being the three cultivation environments (AM1= full sun; AM2= red screen with 50% shading; AM3= black screen with 50% shading), subplot the three substrates (SB1= biochar + soil; SB2= carbonized rice husk + soil; SB3= cattle manure + soil) and the subplot the two irrigation waters (AI1= 0.8 and AI2= 2.5 dS m-1), with four replications of twenty-five seeds. The variables analyzed were: emergence percentage (EP), emergence speed index (ESI), mean time of emergence (MTE), mean speed of emergence (MSE), stem diameter (SD), seedling height (SH) , root length (RL), shoot dry mass (SDM), root dry mass (RDM) and total dry mass (TDM). The AM3 environment presented better conditions for the variables: EP, ESI and MSE. The environment AM2 presented better conditions for the variable MTE with the use of substrates SB2 and SB3 regardless of the salinity of the irrigation water. The SB3 substrate showed better growth conditions for the variables: SH, SD, SDM and TDM. The SB2 substrate provided better conditions for the variable RDM.